Impacts of air pollution on human and ecosystem health, and implications for the National Emission Ceilings Directive: Insights from Italy. (April 2019) - De Marco, Alessandra; Proietti, Chiara; Anav, Alessandro; Ciancarella, Luisella; D'Elia, Ilaria; Fares, Silvano; Fornasier, Maria Francesca; Fusaro, Lina; Gualtieri, Maurizio; Manes, Fausto; Marchetto, Aldo; Mircea, Mihaela; et al.
Abstract: Across the 28 EU member states there were nearly half a million premature deaths in 2015 as a result of exposure to PM2.5, O3 and NO2 . To set the target for air quality levels and avoid negative impacts for human and ecosystems health, the National Emission Ceilings Directive (NECD, 2016/2284/EU) sets objectives for emission reduction for SO2, NOx, NMVOCs, NH3 and PM2.5 for each Member State as percentages of reduction to be reached in 2020 and 2030 compared to the emission levels into 2005. One of the innovations of NECD is Article 9, that mentions the issue of " monitoring air pollution impacts " on ecosystems. We provide a clear picture of what is available in term of monitoring network for air pollution impacts on Italian ecosystems, summarizing what has been done to control air pollution and its effects on different ecosystems in Italy. We provide an overview of the impacts of air pollution on health of the Italian population and evaluate opportunities and implementation of Article 9 in the Italian context, as a case study beneficial for all Member States. The results showed that SO4 2− deposition strongly decreased in all monitoring sites in Italy over the period 1999–2017, while NO3 − and NH4 + decreased more slightly. As a consequence, most of the acid-sensitive sites which underwent acidification in the 1980s partially recovered. The O3 concentration at forest sites showed a decreasing trend. Consequently, AOT40 (the metric identified to protect vegetation from ozone pollution) showed a decrease, even if values were still above the limit for forest protection (5000 ppb h −1 ), while PODy (flux-based metric under discussion as new European legislative standard for forest protection) showed an increase. National scale studies pointed out that PM10 and NO2 induced about 58, 000 premature deaths (year 2005), due to cardiovascular and respiratory diseases. The network identified for Italy contains a good number of monitoring sites (6 for terrestrial ecosystem monitoring, 4 for water bodies monitoring and 11 for ozone impact monitoring) distributed over the territory and will produce a high number of monitored parameters for the implementation of the NECD. Graphical abstract: Unlabelled Image Highlights: NEC Directive set target for emissions of air pollutants for EU Member States. The health impact of air pollution in the EU is expected to be halved by 2030, compared to 2005 levels. NEC Directive is based on impacts of air pollution on ecosystems. A robust monitoring network has been identified in Italy to fulfill the need of the NEC Directive.